Antioxidants versus Food Antioxidant Additives and Food Preservatives - Rafael Franco; Gemma Navarro; Eva Martínez-Pinilla (MDPI AG, 2019)
Natural and processed foods are fragile and can become unpalatable and/or rotten. The processed food industry uses preservatives to enable distribution, even to different continents, and to extend the useful life of their products. Preservatives impede oxidation, a mandatory step in rotting, either by aerobic or anaerobic mechanisms. From a functional point of view, these compounds are antioxidants, and, therefore, a kind of contradiction exists when a preservative is considered “bad” for human health while also thinking that antioxidants provide benefits. The basis of antioxidant action, the doses required for preservation, and the overall antioxidant action are revisited in this work. Finally, the bad and the good of food additives/preservatives are presented, taking into account the main mediator of antioxidant beneficial actions, namely the innate mechanisms of detoxification. Foods that strengthen such innate mechanisms are also presented.